2007
DOI: 10.1152/jn.00841.2006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of Ih by Analgesic Loperamide in Rat DRG Neurons

Abstract: . Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are responsible for the functional hyperpolarization-activated current (I h ) in dorsal root ganglion (DRG) neurons, playing an important role in pain processing. We found that the known analgesic loperamide inhibited I h channels in rat DRG neurons. Loperamide blocked I h in a concentration-dependent manner, with an IC 50 ϭ 4.9 Ϯ 0.6 and 11.0 Ϯ 0.5 M for large-and small-diameter neurons, respectively. Loperamideinduced I h inhibition was unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…The number of potential chemical entities related to I h block is increased by agents that have been shown to block I h in addition to their wellknown primary receptor. For example, it was recently found that loperamide, a potent -opioid-receptor agonist, blocks I h of DRGs with quite high affinity (IC 50 between 5 and 10 M depending on the DRG type) (404). In addition, capsazepine, a well-known inhibitor of the vanilloid-receptor (TRPV1), blocks HCN1 in a concentration-dependent manner (IC 50 ϭ 8 M) (154).…”
Section: B Blockers Of Neuronal I Hmentioning
confidence: 99%
“…The number of potential chemical entities related to I h block is increased by agents that have been shown to block I h in addition to their wellknown primary receptor. For example, it was recently found that loperamide, a potent -opioid-receptor agonist, blocks I h of DRGs with quite high affinity (IC 50 between 5 and 10 M depending on the DRG type) (404). In addition, capsazepine, a well-known inhibitor of the vanilloid-receptor (TRPV1), blocks HCN1 in a concentration-dependent manner (IC 50 ϭ 8 M) (154).…”
Section: B Blockers Of Neuronal I Hmentioning
confidence: 99%
“…10,22 Indeed, the estimated resting membrane potential of HCN1 channelexpressing HEK293H cells on FLIPR was -40 to -45 mV (see Fig. 1), which was significantly different from the test voltage step used in IonWorks recordings (-110 mV; see Methods).…”
Section: Discussionmentioning
confidence: 80%
“…8), whereas randomly selected ICL compounds that were inactive in the MPSD assay did not show any activity on HCN1 channels by IonWorks recordings (data not shown). In addition, we have recently reported a novel pharmacology for loperamide on native HCN channels in DRG neurons, 10 but our observation of the loperamide effect was first made using the HCN blocker MPSD assay followed by confirmation of loperamide functional activity on HCN recombinant channels by IonWorks recordings. 22 Furthermore, the functional activity of selected HCN blockers obtained from ICL screening was confirmed by ex-vivo assay of low magnesium-induced hyperexcitability in rat hippocampal slices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Το φαινόμενο αυτό έχει συσχετισθεί με την εμφάνιση ανοχής και εξάρτησης από τη μορφίνη (190,193,195 Μ, προκάλεσε ισχυρή αναστολή της καλμοδουλίνης (209)(210)(211). Μία άλλη δράση της λοπεραμίδης σε συγκεντρώσεις της τάξης των 10 -6 Μ είναι η αναστολή των εξαρτώμενων από το δυναμικό διαύλων Ca 2+ τύπου L (208,212,239). Σε καλλιέργειες μεσοθηλιακών κυττάρων υπεζωκότα και περικαρδίου ποντικού, φάνηκε ότι οι L δίαυλοι Ca 2+ σε συνεργασία με άλλους μηχανισμούς συμβάλλουν στη διατήρηση της ενδοκυττάριας συγκέντρωσης Ca 2+ , που είναι εξαιρετικά σημαντική σε μεταβολικά ενεργά κύτταρα (229).…”
Section: φυσιολογίαunclassified